Sosialisasi Usaha Mikro Kecil dan Menengah Untuk Masyarakat Desa Ceumeucet Kecamatan Kuta Makmur Kabupaten Aceh Utara - Akli, Zul; M, Muhibuddin; F, Fatahillah; Subaedi, Julman (Yayasan Daarul Huda Kruengmane, 2024)
National Economic Development based on Article 33 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, states that the national economy is structured as a joint effort based on the principle of kinship to achieve prosperity and prosperity for Micro, Small and Medium Enterprises (MSMEs). Realizing the important role of MSMEs, efforts are made to empower MSMEs in the context of accelerating regional and central economic development as well as increasing the competitiveness of MSME products. Social welfare, as a desired condition, cannot be realized if it is not developed through social welfare efforts, whether by the government, non-governmental organizations, or the business world. This community service is carried out using socialization methods, lectures, discussions, questions and answers as well as legal education regarding the Socialization of Micro, Small and Medium Enterprises for the Community of Ceumeucet Village, Kuta Makmur District, North Aceh Regency. The results of this counseling are that Micro, Small and Medium Enterprises can improve their MSME businesses in Gampong Ceumeucet, Kuta Makmur District, North Aceh Regency, they can develop their business products to a much greater extent by utilizing various existing technologies and building a technologically sound MSME product identity so that they can growing rapidly among the wider community.